Hyperglycemia recognised in early pregnancy is phenotypically type 2 diabetes mellitus not gestational diabetes mellitus: a case control study. (1st December 2020) - Agha-Jaffar, Rochan; Oliver, Nick S.; Kostoula, Melina; Godsland, Ian F.; Yu, Christina; Terry, Jayne; Johnston, Desmond; Gable, David; Robinson, Stephen
Abstract: Objective: Gestational diabetes mellitus is defined as "diabetes recognized in the second or third trimester that is not clearly overt diabetes". Evidence relating to women with hyperglycemia early in pregnancy is limited. We aimed to evaluate women diagnosed with hyperglycemia early in pregnancy (eGDM) and compared them to those with pregestational established type 2 diabetes mellitus (T2DM) and gestational diabetes diagnosed routinely at 24–28-week gestation (rtGDM) to determine if the length of exposure to hyperglycemia adversely affected outcomes. Methods: Forty consecutive women with eGDM who attended a multidisciplinary antenatal clinic were reviewed. Two separate BMI-matched control groups were identified, recognized pregestational T2DM ( n = 80) and rtGDM ( n = 80). Baseline demographics and outcomes were compared. Results: A higher proportion of women in the eGDM and T2DM group required insulin and the incidence of hypertensive disorders was similarly increased compared with the rtGDM group (88.6, 77.0 versus 8.1%, p < .001 and 42.5%, 37.5 versus 12.5% p < .001, respectively). The proportion of infants born small for gestational age varied (eGDM 11.1%, T2DM 13.0%, and rtGDM 2.5%, p =.049). Postpartum, 7.5% of eGDM women were diagnosed with T2DM versus 1.3% in the rtGDM group ( p <.001). Conclusions: These novel data demonstrate that the length of exposure to glucose adversely affects materno-foetal outcomes independent of maternal adiposity.